2013
DOI: 10.1186/1471-2458-13-141
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of overweight among adolescents in Ho Chi Minh City, Vietnam

Abstract: BackgroundTwo previous surveys conducted in Ho Chi Minh City revealed an increasing prevalence of overweight and obese adolescents, from 5.9% in 2002 to 11.7% in 2004. From 2004 to 2010, the government set up and implemented health promotion programs to promote physical activity and good nutritional habits in order to prevent overweight and obesity in children and adolescents. Our study aimed to estimate the prevalence of overweight and obesity among adolescents in urban areas of Ho Chi Minh City in 2010.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 19 publications
3
43
2
1
Order By: Relevance
“…The prevalences of OW/OB among 11-to 12-year-old students in central Hanoi were quite high compared with the data from other studies in Hanoi and Ho Chi Minh City in Vietnam [16,17]. This study also found that several characteristics of the children, their families, and their lifestyle behaviours were strongly associated with the risks of OW/OB.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…The prevalences of OW/OB among 11-to 12-year-old students in central Hanoi were quite high compared with the data from other studies in Hanoi and Ho Chi Minh City in Vietnam [16,17]. This study also found that several characteristics of the children, their families, and their lifestyle behaviours were strongly associated with the risks of OW/OB.…”
Section: Resultscontrasting
confidence: 41%
“…That previous survey included participants aged 7-9 years and found rates of overweight and obesity of 23.4 and 17.3%, respectively [16]. Another study in 2010 that included adolescents aged 11-14 years old in Ho Chi Minh City found rates of overweight and obesity of 19.6 and 7.9%, respectively [17]. Obesity is a risk factor for NCDs, and Vietnam has been identified as a country with a major problems associated with NCDs, which are responsible for approximately 73% of total deaths [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of overweight and obesity among children in Vietnam is increasing, especially in urban areas. A study found that the prevalences of overweight and obesity among children aged 11-14 in a large city were 17.8% and 3.2%, respectively [15]. Therefore, this study is aimed at estimating the prevalence of type 1 and type 2 diabetes and prediabetes among Vietnamese children aged 11-14 and examining associated factors of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…C hildhood and adolescent overweight and obesity have increased rapidly in both developed and developing countries 1,2,3,4 . Obesity rates in children and adolescents in Thailand were 5.8%, 6.7%, and 9.7% in 1995, 2001, and 2008-2009, respectively 5 .…”
Section: Introductionmentioning
confidence: 99%